Effect of Electrolyte Concentration and Nafion Membrane Separators on Discharge Dynamics and Voltage Stability of Supercapacitors - Saddam Dhobi; Jagendra Chaudhari; Sangita Rai (Universitas Negeri Semarang, 2026)
This study investigates the effects of Na₂SO₄ electrolyte concentration and Nafion membrane separators on the self-discharge behavior, discharge dynamics, capacitance, and voltage stability of supercapacitors, aiming to identify optimal conditions for enhanced charge retention and long-term energy storage. Supercapacitors were fabricated with Nafion separators and charged at different voltages (1.0, 1.2, and 1.4 V) for varying durations (1, 1.5, and 2 minutes). Self-discharge was monitored, capacitance was calculated using the capacitor discharge equation, and discharge tests were conducted through a 500-ohm resistor to simulate realistic operating conditions. The results demonstrate that supercapacitors with Nafion separators and 0.5 M Na₂SO₄ electrolyte exhibit significantly lower self-discharge rates and more stable voltage profiles compared with those using napkin paper separators. Additionally, higher charging voltages and longer charging times improve charge retention. These findings indicate that the combination of Nafion membranes and optimized electrolyte concentration effectively enhances supercapacitor performance, providing a practical strategy for reliable and efficient energy storage applications.